2001
DOI: 10.1038/sj.ijo.0801536
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for obesity-induced increase in myocardial lipid peroxidation

Abstract: OBJECTIVE:To determine the mechanisms underlying the obesity-induced increase in myocardial lipid peroxidation in the faafa rat. We hypothesized that elevated heart work (ie rate-pressure product), an increased rate of superoxide (O 2 À ) production, total myocardial lipid content, andaor insuf®cient antioxidant defenses are potential contributors to myocardial lipid peroxidation in obesity. DESIGN: Comparative, experimental study of myocardial tissue in 16-week-old lean control (Faa?, normal diet), obese high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 36 publications
9
94
0
4
Order By: Relevance
“…Increased fatty acid uptake and oxidation by the heart can also increase MV O 2 , because more oxygen is required to generate ATP from fatty acid than by glucose metabolism, and increased oxygen may be consumed by fatty acid esterification and reactive oxygen species production. 8,10,27 Our finding that increasing BMI was an independent predictor of decreased efficiency extends the findings of previous ex vivo studies to obese humans. These previous studies demonstrated that increased MV O 2 , MFAUp, and MFAO were associated with decreased efficiency.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Increased fatty acid uptake and oxidation by the heart can also increase MV O 2 , because more oxygen is required to generate ATP from fatty acid than by glucose metabolism, and increased oxygen may be consumed by fatty acid esterification and reactive oxygen species production. 8,10,27 Our finding that increasing BMI was an independent predictor of decreased efficiency extends the findings of previous ex vivo studies to obese humans. These previous studies demonstrated that increased MV O 2 , MFAUp, and MFAO were associated with decreased efficiency.…”
Section: Discussionsupporting
confidence: 79%
“…6,7 Other data from studies conducted in animals demonstrate that increased fatty acid availability and myocardial lipid content predispose the myocardium to increased oxidative stress and myocardial injury. 10,11 It is not known whether the changes in myocardial fatty acid metabolism and efficiency observed in animal models of obesity and insulin resistance also occur in humans. Therefore, the purpose of the present study was to determine the effect of obesity and insulin resistance in women on myocardial fatty acid metabolism, oxygen consumption, and efficiency.…”
mentioning
confidence: 99%
“…Finally, myocardial lipid content is also increased in lean Zucker rats fed a high-fat diet and is associated with myocardial oxidative injury. 24 As for obese humans, lipid excess in the myocardium, as assessed by magnetic resonance spectroscopy, has been demonstrated and correlates with left ventricular mass and systolic dysfunction. 25 In summary, genetic rodent models of obesity and dietinduced obesity in rodents and humans show cardiac lipid accumulation within myocytes.…”
Section: Ectopic Fat Storage In the Heartmentioning
confidence: 99%
“…53 It has been proposed that in the early stages of obesity there may be an initial elevation in antioxidant enzymes to counteract oxidative stress, whereas chronic obesity continually depletes the sources of antioxidant enzymes. 23,54 The degree of adiposity also affects enzyme activities. In a cross-sectional study, Olusi 23 found that erythrocyte CuZn-SOD activity was lower in the very obese (853 vs 1464 U/g Hb), and GPX activity was lower in the obese (76 vs 98.4 U/g Hb) than in the nonobese controls.…”
mentioning
confidence: 99%